Sustainability Implications of the Incorporation of a Biogas Trapping System into a Conventional Crude Palm Oil Supply Chain - Lim, C.; Biswas, Wahidul (M D P I AG, 2019)
This paper presents the sustainability implications of installing biogas trapping systems in palm oil mills of a crude palm oil production supply chains in Malaysia. The study evaluates the impact of this mitigation strategy on the existing supply chains published by Lim and Biswas. The experience of a local palm oil mill installed with the KUBOTA biogas trapping system was incorporated into a typical 60 metric tonne per hour palm oil mill for effluent treatment. This allowed us to assess the changes in sustainability performance of the whole crude palm oil supply chain using the Palm Oil Sustainability Assessment (POSA) framework. Installing the biogas trapping system increased waste recycling and reuse percentage of the mill from 81.81% to 99.99% and the energy ratio (energy output/fossil fuel and biomass energy input) from 2.45 to 2.56; and reduced the Greenhouse Gas emission of the supply chain from 0.814 tonne CO2eq to 0.196 tonne CO2eq per tonne of Crude Palm Oil. This system could also potentially increase the mill’s annual revenue by 2.3%, while sacrificing the sustainability performance of other economic indicators (i.e., a further 3% negative deviation of actual growth rate from sustainable growth rate). Overall, sustainability score of the supply chain improved from 3.47/5 to 3.59/5 on the 5-level-Likert-scale due to environmental improvement strategy consideration. Finally, this paper shows that the POSA framework is capable of capturing changes in the sustainability performance of triple bottom line indicators associated with the use or incorporation of any improvement strategy in the crude palm oil supply chain.